Antibacterial and antiviral roles of a fish β-defensin expressed both in pituitary and testis. - Jun-Yan Jin (Public Library of Science (PLoS), 2010)
Defensins are a group of cationic peptides that exhibit broad-spectrum antimicrobial activity. In this study, we cloned and characterized a β-defensin from pituitary cDNA library of a protogynous hermaphroditic orange-spotted grouper (Epinephelus coioides). Interestingly, the β-defensin was shown to be dominantly expressed in pituitary and testis by RT-PCR and Western blot analysis, and its transcript level is significantly upregulated in reproduction organs from intersexual gonad to testis during the natural and artificial sex reversal. Promoter sequence and the responsible activity region analyses revealed the pituitary-specific POU1F1a transcription binding site and testis-specific SRY responsible site, and demonstrated that the pituitary-specific POU1F1a transcription binding site that locates between -180 and -208 bp is the major responsible region of grouper β-defensin promoter activity. Immunofluorescence localization observed its pituicyte expression in pituitary and spermatogonic cell expression in testis. Moreover, both in vitro antibacterial activity assay of the recombinant β-defensin and in vivo embryo microinjection of the β-defensin mRNA were shown to be effective in killing gram-negative bacteria. And, its antiviral role was also demonstrated in EPC cells transfected with the β-defensin construct. Additionally, the antibacterial activity was sensitive to concentrations of Na(+), K(+), Ca(2+) and Mg(2+). The above intriguing findings strongly suggest that the fish β-defensin might play significant roles in both innate immunity defense and reproduction endocrine regulation.